PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) IPABERBASIS MODEL PROBLEM BASED LEARNING (PBL) DI KELAS - Sayyida Nafisa; Muhamad Rohadi; Ali Ahmad; Akmal Fadhillah; Maura Febrianti Z; Yulia Rahmadhar (CV. Denasya Smart Publisher, 2025)
This study aims to discus development of Student Worksheets (LKPD) based on the Problem Based Learning (PBL) model to enhance student engagement and activity in science learning. Through a Research and Development approach, this study identifies the needs and requirements for creating effective LKPD. The methods employed include the Define, Design, Develop, and Disseminate phases. The findings indicate that the developed LKPD encourages students to actively participate, think critically, and collaborate in groups. Thus, the use of PBL-based LKPD is expected to improve student learning outcomes and the overall quality of education.